Dietary Pyridoxine Controls Efficacy of Vitamin B6-Auxotrophic Tuberculosis Vaccine Bacillus Calmette-Guérin ΔureC::hly Δpdx1 in Mice - Martin Gengenbacher (American Society for Microbiology, 2014)
ABSTRACT The only tuberculosis (TB) vaccine in use today, bacillus Calmette-Guérin (BCG), provides insufficient protection and can cause adverse events in immunocompromised individuals, such as BCGosis in HIV+ newborns. We previously reported improved preclinical efficacy and safety of the recombinant vaccine candidate BCG ΔureC::hly, which secretes the pore-forming listeriolysin O of Listeria monocytogenes. Here, we evaluate a second-generation construct, BCG ΔureC::hly Δpdx1, which is deficient in pyridoxine synthase, an enzyme that is required for biosynthesis of the essential cofactor vitamin B6. This candidate was auxotrophic for vitamin B6 in a concentration-dependent manner, as was its survival in vivo. BCG ΔureC::hly Δpdx1 showed markedly restricted dissemination in subcutaneously vaccinated mice, which was ameliorated by dietary supplementation with vitamin B6. The construct was safer in severe combined immunodeficiency mice than the parental BCG ΔureC::hly. A prompt innate immune response to vaccination, measured by secretion of interleukin-6, granulocyte colony-stimulating factor, keratinocyte cytokine, and macrophage inflammatory protein-1α, remained independent of vitamin B6 administration, while acquired immunity, notably stimulation of antigen-specific CD4 T cells, B cells, and memory T cells, was contingent on vitamin B6 administration. The early protection provided by BCG ΔureC::hly Δpdx1 in a murine Mycobacterium tuberculosis aerosol challenge model consistently depended on vitamin B6 supplementation. Prime-boost vaccination increased protection against the canonical M. tuberculosis H37Rv laboratory strain and a clinical isolate of the Beijing/W lineage. We demonstrate that the efficacy of a profoundly attenuated recombinant BCG vaccine construct can be modulated by external administration of a small molecule. This principle fosters the development of safer vaccines required for immunocompromised individuals, notably HIV+ infants. IMPORTANCE Mycobacterium tuberculosis can synthesize the essential cofactor vitamin B6, while humans depend on dietary supplementation. Unlike the lipophilic vitamins A, D, and E, water-soluble vitamin B6 is well tolerated at high doses. We generated a vitamin B6 auxotroph of the phase II clinical tuberculosis vaccine candidate bacillus Calmette-Guérin ΔureC::hly. The next-generation candidate was profoundly attenuated compared to the parental strain. Adaptive immunity and protection in mice consistently depended on increased dietary vitamin B6 above the daily required dose. Control of vaccine efficacy via food supplements such as vitamin B6 could provide a fast track toward improved safety. Safer vaccines are urgently needed for HIV-infected individuals at high risk of adverse events in response to live vaccines.